Three Intervention Programs in Secondary Education on Attitudes Toward Persons With a Disability - Álvarez-Delgado, Julián; León-del-Barco, Benito; Polo-del-Río, María-Isabel; Mendo-Lázaro, Santiago; Lopez-Ramos, Victor M. (Frontiers in Psychology, 2022)
Persons with a disability make up a social group which is in an especially vulnerable situation. They have to face obstacles and difficulties in their participation as part of the community with equal opportunities, in which attitude of others is a determining factor. This study makes a comparative analysis of three intervention programs (1 “Simulation and Modeling,” 2 “Information and Awareness Raising,” and 3 “Adapted Sport”) on attitudes toward persons with a disability of adolescents in secondary schools. Each program is based on a concrete technique, but they all have the common thread of the direct, structured contact technique with persons with a disability. The effectiveness of the three programs in changing attitudes is analyzed, and their impact on the different factors of the attitude construct (1 “acceptance/rejection,” 2 “competence/limitation,” and 3 “equality of opportunities”) is also studied. The results show the effectiveness of the three programs. The students show more positive attitudes toward persons with a disability in all the groups, especially program 1. Analyzing the general influence of the three programs on the factors of the attitude construct, it can be seen that in factors 2 and 3, the attitudes have significantly improved in all three programs. Finally, the results show that each program has been more effective on a concrete attitude factor.